CSR Mediation in the Effect of Green Accounting on Company Performance - Nadi Saputri, Ni Made Pratiwi; Handajani, Lilik (E-Jurnal Akuntansi; Vol 34 No 7 (2024)DO - 10.24843/EJA.2024.v34.i07.p07, 2024)
This research aims to evaluate the impact of green accounting on corporate performance with the mediating role of corporate social responsibility (CSR) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018 - 2022. The research population includes manufacturing companies listed on the IDX during the same period. Using purposive sampling , 46 samples were obtained, consisting of manufacturing companies that have consistently paid dividens for the past five years. This research employs quantitative data analysis methods and utilizes E-Views software for descriptive statistical analysis, classical assumption tests, path analysis, and hypothesis testing. The results indicate that CSR does not mediate the relationship between green accounting and company performance of manufacturing companies listed on the IDX from 2018 to 2022. The allocation of Environmental costs by the companies has not yielded positive results because companies have yet managed to reduce potential future liabilities. CSR functions merely as a social responsibilityand has not yet been able to provide sustainable environmental impact. reduce potential future liabilities. Keywords: corporate social responsibility, green accounting, company performance